An improved model for the time-dependent material response of wood under mechanical loading and varying humidity conditions. (15th May 2022) - Yu, Taoyi; Khaloian, Ani; van de Kuilen, Jan-Willem
Highlights: A review on performance of the existing wood rheological models is provided. A 3D orthotropic elatic-plastic viscoelastic mechano-sorptive model is developed. Transcending mechano-sorptive creep and complex recovery is captured. The model is validated for different species, load directions, and moistening history. Sensitivity analysis is performed to generalize the material behavior. Abstract: Timber is one of the most widely applied engineering materials due to its favorable physical and mechanical characteristics. Nevertheless, over the service life, the combination of mechanical load and varying environmental conditions can have a critical influence on the mechanical response of timber structures, considering especially the mechano-sorptive characteristics. In this work, the performance analysis of the existing time- and moisture-dependent models identifies the need of a more comprehensive 3D constitutive rheological model, which can take into account orthotropic, elastic-plastic, viscoelastic and mechano-sorptive aspects, including the complex mechano-sorptive recovery phases that may occur over the lifetime. Therefore, a comprehensive algorithm of such a model is developed here. An improvement is made for the mechano-sorptive component by introducing an ordinary and a transcending mechano-sorptive part, which are governed by the absolute change of moisture content and the change exceeding the historical highest moisture content at each loading phase, respectively. Simulations are run under cases with mechanical loading of tension and compression perpendicular and parallel to the direction of the fibers. Both medium-term (up to 2500 h) as well as short-term (up to 350 h) mechanical behavior of the material under constant temperature is analyzed and good agreements are achieved with literature results. Comparison with existing models indicates that the proposed model gives an improved prediction of the mechano-sorptive creep and recovery, which has a non-linear dependence on the moisture history. Furthermore, sensitivity analyses are performed and the applicability of the model to different species under different combinations of load and moisture variation is studied here.